A Seat at the Table: Distributional impacts of food-price increases due to climate change - Nada Maamoun; Caroline Grünhagen; Hauke Ward; Ulrike Kornek (ZBW – Leibniz Information Centre for Economics, 2024)
Although climate change is expected to have a significant impact on the global population, little is known about how it will affect individual households in their daily lives. Based on food price increases caused by climate change, we analyse how climate-change-related damages distribute across households in over 75 developing countries. In a microsimulation model, climate damages are quantified as losses in consumer surplus, on average roughly 3 percent of total expenditure. We find evidence that climate damages are regressive, i.e. they disproportionately affect households with lower consumption. Damages display regressivity when we compare (a) national averages across countries, (b) all households in our sample, and (c) households within countries. However, there are some - often more developed - countries, where damages are progressive, i.e. damages disproportionately affect more affluent households in those countries. At a sectoral level, damages tend to be more regressive in countries where in relative terms rice consumption contributes more to the welfare of households.
Keywords: Q54; D63; D31; 330; Climate damages; Distributional impacts; Food prices; Regressivity